Caesarean section with breech presentation and shaft femur fracture in newborn: a rare case report - Tiwary, Rimple; Tiwary, Manish Kumar (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Vaginal delivery for breech presentation is always associated with a higher risk of injury to the newborn as compared to caesarean delivery. A male infant was delivered by elective caesarean section at 40 weeks of gestation for breech presentation. During extraction, the newborn sustained a right femur shaft fracture. A simple splint with immobilization along with leg raise led to complete healing without complication. Caesarean delivery is associated with a reduced risk of newborn birth injuries as compared to vaginal and instrumental delivery but rare accidental complication can be possible.